2016
DOI: 10.15408/sdi.v23i1.2808
|View full text |Cite
|
Sign up to set email alerts
|

Leadership and Ideological Bond: PPP and Internal Fragmentation in Indonesia

Abstract: During 2014-2016, the United Development Party (PPP) experienced the most severe and prolonged internal fragmentation in its history. Since the beginning of 2014, the emergence of the twin Board of the Central Committee cemented the fragmentation that had occurred. Some people relate this phenomenon to the interests of the elites. However, the interest of the elites itself is something inevitable and in many cases is not necessarily the cause for prolonged fragmentation. e aim of this article, therefore, is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…Internal conflict is inevitable as a result of the contradictory views and interests that occurred among the party elites, and the disillusioned elites urge you to leave and form new parties. Noor (2016), who scrutinized the PPP internal conflict in 2014, revealed that the leadership weakness and the strong elites' interest have a role in creating the intra-party conflict. Those studies seem to agree that the inner conflict and fragmentation has degraded the Islamic-based parties' electoral performance.…”
Section: Introductionmentioning
confidence: 99%
“…Internal conflict is inevitable as a result of the contradictory views and interests that occurred among the party elites, and the disillusioned elites urge you to leave and form new parties. Noor (2016), who scrutinized the PPP internal conflict in 2014, revealed that the leadership weakness and the strong elites' interest have a role in creating the intra-party conflict. Those studies seem to agree that the inner conflict and fragmentation has degraded the Islamic-based parties' electoral performance.…”
Section: Introductionmentioning
confidence: 99%
“…Kecenderungan konflik internal pada PPP ini bukan disebabkan karena perbedaan visi-misi, flatform, dan ideologi partai, tetapi cenderungan disebabkan oleh pragmatisme atas pilihan koalisi partai politik dalam mendukung calon presiden dan wakil presiden dan/atau pemerintahan. Ciri utama dari perpecahan parpol umumnya dimulai dengan konflik antar elit terkait dengan sikap mereka terhadap strategi dalam merebut kekuasan(Noor 2016) Perpecahan ini muncul diakibatkan terdapat dua Faksi di PPP, yakni faksi yang ingin tetap pada koalisi oposisi diluar pemerintahan, dan faksi yang ingin menjadi bagian didalam pemerintahan, yang pada akhirnya menimbulkan pembelahan PPP. Dinamika perpecahan semakin berkembang dan meluas ketika muncul Muktamar Surabaya secara aklamasi memilih Romahurmuziy sebagai ketua Umum, dan sementara Muktamar Jakarta menetapkan secara aklamasi juga Djan Faridz sebagai Ketua Umum.…”
unclassified